TEMPORAL PATTERN OF WORK-FAMILY CONFLICT DEPRESSION EXPERIENCED BY BANK EMPLOYEES IN ENUGU STATE, NIGEIRA - Ugwu, D.I. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The study determined level of work-family conflict depression and the temporal pattern of work-family conflict depression experienced based on season (rainy and dry seasons) among bank employees in Enugu State, Nigeria. Four hundred and seventy-seven bank employees participated in the study. Two instruments were used to generate data for the study. They are: the adapted 13-item Work-family Conflict Depression Inventory (WFCSI) developed by Zung (1965) and the Key Informant Interview Schedule (KlIS) that was developed by the researcher. Mean, Percentages and Chi-square statistics were used for data analysis. The result indicated that bank employees experienced moderate level of work-family depression; higher proportion of employees experienced work-family conflict depression during the rainy season than during the dry season. The finding also revealed that there was no significant difference in the levels of work-family conflict depression experienced by bank employees during the rainy and during the dry seasons. Based on the findings, it was recommended among others that management should try to adopt work-family mitigating measures such as training, counselling, work shift and periodic test that will help bring employees health at optimal level and help foster good work-family balance at all seasons.